The NT-ProBNP Test in Subjects with End-Stage Renal Disease on Hemodialysis Presenting with Acute Dyspnea: Is Knowing Worth the Cost? - Shaffer R. S. Mok; Jose Avila; Barry Milcarek; Richard Kasama (Emergency Medicine International)
Background. The NT-ProBNP/BNP test has been validated as a marker for determining the etiology of acute dyspnea. In the setting of end-stage renal disease on hemodialysis (ESRD on HD), the utility of the NT-ProBNP/BNP test has not been validated. This study examines the clinical utility of the NT-ProBNP test in the setting of ESRD on HD patients presenting with acute dyspnea. Methods. A retrospective case series of 250 subjects were admitted to Cooper University Hospital, 07/2010-03/2011, with ESRD and HD presenting with dyspnea. The incidences of echocardiography, cardiology consultation, and NT-ProBNP elevated and normal were examined. Correlation coefficients were calculated for NT-ProBNP with age (years), estimated dry weight (kg), amount of fluid removed (L), and ejection fraction (EF in %) among other echocardiography parameters. Results. Of the total sample 235 patients had NT-ProBNP levels performed. Cardiology consults were placed in 68.8% and 58% who underwent echocardiography. Of those for whom an echocardiography was performed estimated mean EFs of 54.6%, 50.8%, and 61.7% were observed among the NT-ProBNP elevated group, normal group, and no NT-ProBNP group, respectively. No differences were detected in all other echocardiography measurements. No correlation was observed between NT-ProBNP and age (), baseline EDW (), amount of fluid removed (), or EF (). Conclusion. In the setting of ESRD on HD, the NT-ProBNP test has no clinical utility in determining the etiology of acute dyspnea. This can be demonstrated through echocardiographic and therapeutic parameters measured in this study.